Sex-Specific Modulation of the Host Transcriptome in the Spleen of Schistosoma mansoni-Infected Mice - Winkelmann, Franziska; Rabes, Anne; Reinholdt, Cindy; Koslowski, Nicole; Koczan, Dirk; Reisinger, Emil C.; Sombetzki, Martina (Frontiers in Cellular and Infection Microbiology, 2022)
Background Schistosomiasis is a severe parasitic disease that is primarily driven by the host’s immune response to schistosome eggs trapped in tissue and by the granulomatous inflammatory and fibrotic reaction they cause. Despite significant progress in understanding the complex immunological processes involved in the relationship between schistosomes and their host, neither an effective vaccine against the infection nor anti-fibrotic drugs currently exists, making the search for new targets for schistosome drugs and vaccine candidates even more important. In order to identify new molecular targets for defense against or elimination of the parasite, we investigate herein the interplay between the host and male or female schistosomes, clearly separating this from the action of the parasite eggs. Methods For this purpose, we infected 6–8-week-old female NMRI mice with 100 male (M), female (F), or both (MF) S. mansoni cercariae and performed a comparative transcriptomic and flow cytometric analysis of their spleens. Results Principal component analysis of a total of 22,207 transcripts showed a clear clustering of the experimental groups. We identified a total of 1,293 genes in group M, 512 genes in group F, and 4,062 genes in group MF that were differentially expressed compared to naive controls. The highest percentage of regulated genes (2,972; 65.9%) was found in group MF alone, but there was a large overlap between groups M and MF (798; 17.7%) and a small overlap between groups F and MF (91; 2.0%). Only 4.5% of genes (201) were revealed to be regulated in all experimental groups (M/F/MF). In addition, we were able to show that both worm sexes trigger immune responses in an egg-independent manner (non-polarized Th1 and Th2 response), with female worms exerting less regulatory influence than males. Conclusion Our data show that adult schistosomes trigger sex-specific, egg-independent immune responses. The lists of genes regulated by adult female or male worms presented here may be useful in deciphering host–parasite interactions to identify targets for schistosome elimination.